CAN COLLECTIVE EMOTIONS IMPROVE BITCOIN VOLATILITY FORECASTS? - BOURGHELLE, David; JAWADI, Fredj; ROZIN, Philippe (Bankers, Markets & Investors, 2022)
This paper extends the study of Bourghelle et al. (2022) to check whether collective emotions could help forecast bitcoin volatility over the period 2018-2021. To this end, we first assess whether consideration of investor sentiment and collective emotions can give us clearer insights into bitcoin dynamics over the period in question and whether it can help to explain the different shifts in price. Formally, we ran causality tests and, as in Bourghelle et al. (2022), built a two equation nonlinear vector autoregressive (VAR) model to assess for further lead-lag effects between bitcoin volatility and collective emotions. Second, we proposed in-sample forecasts of bitcoin volatility to test whether it would be possible to improve our forecasts by taking investors’ emotions and sentiment into account. Our findings show that market sentiment and investors’ emotions provide useful information that can explain shifts, structural breaks, and changes in bitcoin volatility. Further, collective emotions improve bitcoin volatility forecasting as our nonlinear model, including emotions-related news, supplants the benchmark linear model.